Potential of Quercetin as a Promising Therapeutic Agent Against Type 2 Diabetes - Przemysław Niziński; Anna Hawrył; Paweł Polak; Adrianna Kondracka; Tomasz Oniszczuk; Jakub Soja; Mirosław Hawrył; Anna Oniszczuk (Molecules)
Quercetin (QE) is a naturally occurring flavonoid found in many fruits, vegetables, and other plant-based foods. It is recognized for its diverse pharmacological activities. Among its many therapeutic potentials, its antidiabetic properties are of particular interest due to the growing worldwide prevalence of diabetes mellitus. QE improves glycemic control by enhancing insulin sensitivity, stimulating glucose uptake, and preserving pancreatic beta cell function. These effects are mediated by the modulation of key molecular pathways, including AMPK, PI3K/Akt, and Nrf2/ARE, as well as by the suppression of oxidative stress and pro-inflammatory cytokines, such as TNF-α and IL-6. Furthermore, QE mitigates the progression of diabetic complications such as nephropathy, retinopathy, and vascular dysfunction, reducing lipid peroxidation and protecting endothelial function. However, the clinical application of quercetin is limited by its low water solubility, poor bioavailability, and extensive phase II metabolism. Advances in formulation strategies, including the use of nanocarriers, co-crystals, and phospholipid complexes, have shown promise in improving its pharmacokinetics. This review elucidates the mechanistic basis of QE quercetin antidiabetic action and discusses strategies to enhance its therapeutic potential in clinical settings.